An excess of niche differences maximizes ecosystem functioning - Godoy, Oscar; Gómez-Aparicio, Lorena; Matías, Luis; Pérez-Ramos, Ignacio M.; Allan, Eric (Nature communications, 2020)
Ecologists have long argued that higher functioning in diverse communities arises from the niche differences stabilizing species coexistence and from the fitness differences driving competitive dominance. However, rigorous tests are lacking. We couple field-parameterized models of competition between 10 annual plant species with a biodiversity-functioning experiment under two contrasting environmental conditions, to study how coexistence determinants link to biodiversity effects (selection and complementarity). We find that complementarity effects positively correlate with niche differences and selection effects differences correlate with fitness differences. However, niche differences also contribute to selection effects and fitness differences to complementarity effects. Despite this complexity, communities with an excess of niche differences (where niche differences exceeded those needed for coexistence) produce more biomass and have faster decomposition rates under drought, but do not take up nutrients more rapidly. We provide empirical evidence that the mechanisms determining coexistence correlate with those maximizing ecosystem functioning. It is unclear how biodiversity-ecosystem functioning and species coexistence mechanisms are linked. Here, Godoy and colleagues combine field-parameterised competition models with a BEF experiment to show that mechanisms leading to more stable species coexistence lead to greater productivity, but not necessarily to enhanced functions other than primary production.